The Comparative Study of Archipelago's Islamic Civilization History: Analysis of Socio-cultural Development in Indonesia and Malaysia - Puji Azizah, Faras; Hakim, Lukmanul; Erasiah (Qurthuba: The Journal of History and Islamic Civilization, 2024)
The purpose of this article is to discuss the history of Islamic civilization in Indonesia and Malaysia before and after independence. It is known that Indonesia and Malaysia are allied, and both are Islamic-majority countries. In this case, the method used in this paper is a literature study approach. The writer collects sources from articles, journals, books, and similar writings relevant to this research. The results of this paper say that Islam entered Indonesia in the 7th century and Malaysia in the 9th century, which was the initial stage of the formation of a Muslim community consisting of traders. Furthermore, there have been Islamic-style kingdoms that are the result of the spread of Islam. And it should be noted that Islam entered Malaysia and Indonesia peacefully without war.